Effect of Incandescent Light on Collection of West Nile Virus Vectors Using CDC Miniature Light Traps in Northern Colorado. Issue 5 (4th October 2021) - Boze, Broox G V; Renfro, Kelsey; Markowski, Daniel; Lozano-Fuentes, Saul
Abstract: To evaluate whether the presence of clear incandescent light was attractive or refractive to host-seeking mosquitoes in northern Colorado, a Bayesian hierarchical model was created to measure differences in trap effectiveness based on presence or absence of phototactic cues. A total of eight CDC miniature light traps (with and without light) were set weekly across four locations in northern Colorado between Weeks 23 and 32 of year 2020. Culex mosquitoes (Diptera: Culicidae) accounted for 81% of all collections in this study with two vectors of West Nile virus being represented. The probability of catching both Culex tarsalis Coquillett and Culex pipiens Linnaeus was reduced when traps were equipped with light, but the difference was not statistically significant for Culex tarsalis . The clear reduction in the number of Culex pipiens caught when these traps were equipped with light indicates negative phototactic behavior and underestimation with current surveillance strategies. Removal of light from these traps may aid our understanding of these species' distribution within the environment, improve collection efficiency, and help guide implementation of targeted control measures used in public health mosquito control.